EFL instructors’ values systems, reflections and emotions on paired peer observation process - Bayındır Özkan, Fatma Yasemin; Dikilitaş, Kenan (Pedagogical Perspective, 2024)
It is a fact that teachers worldwide are aiming at one thing and one thing only: students’ success. To this end, teachers must continue learning and developing their skills. It is necessary to engage in self-evaluation through some activities, which include collaboration, interaction and reflection. One way of achieving this is to have peer observations, which enable teachers to focus on a ‘problematic area’ of their teaching with a colleague. However, teachers often perceive peer observations negatively as they resonate with institutional observations.  This study aims to investigate EFL instructors’ value systems, emotions, and reflections on paired peer observation in higher education. For this purpose, eight EFL instructors at a foundation university in Turkey were interviewed about their existing beliefs, attitudes, and values. Then, the pairs observed each other and were again interviewed to explore the changes in their value systems and to study the emotions that emerged in each step of the process, which constitutes a gap in the literature. Finally, they were asked to write reflective essays to examine the impact of observing each other on their reflectivity and professional development. Findings indicate a change in instructors’ existing beliefs on the ideal partner and an increase in their willingness to continue doing paired peer observations as they increase collegiality between the partners and enhance their motivation and self-efficacy. Also, the participants' negative emotions towards peer observation were quickly replaced with positive ones once the observation happened. An unexpected finding is that the participants found giving feedback to their partners harder than receiving feedback. The suggested ground rules to have a smooth observation activity can be implemented.